TEACHING VOCABULARY BY USING PICTURE - F42107029, Gine Rahmadani Gemilang; Buan, Stevanus; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2012)
Picture as media in teaching vocabulary which are learning and enhancement students in acquire the language. The purpose of this research is to know whether teaching vocabulary to the seventh grade student of SMPN 1 Sungai Betung in academic year 2011/2012 through picture is effective. The methodology is through pre-experimental study, using a measurement technique in form of label the picture, complete sentence and change the picture in to word in the sentence which consists of 20 test items. Based on the data analysis, mean score of pre-test is 3.97, qualifying poor and post-test mean score is 7.22, qualifying average to good. Teaching vocabulary through pictures effectively improve the students achievement of vocabulary. Keywords: Vocabulary, picture, achievement